Istota i rodzaje systemów emerytalnych - Dybał, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The main goal of the article is to present the nature and types of pension schemes. A number of criteria characterizing the pension systems were presented in the article. The author tried to present a taxonomy of pension systems implemented in different countries. To obtain the aim, the most common method of classification proposed by the International Labour Organisation, World Bank, Organization for Economic Cooperation and Development was used. As a result, pension systems in different countries are varied. This is due to differences in legal, social and economic factors that affect the shape of the pension system in the country
Keywords: emerytury; programy emerytalne; system emerytalny